PENERAPAN ASAS EQUALITY BEFORE THE LAW DALAM BEBERAPA PUTUSAN PENGADILAN PADA PERKARA TINDAK PIDANA KORUPSI DI INDONESIA - Wifra Hadhratin; Erdianto Erdianto; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
There are differences in treatment in terms of differences in the placement ofdefendants by the Court (Judge) as law enforcement officers who have the authoritydetermined by law. This shows that there is objective law enforcement. There is still anoverlap in the judge's decisions that have been determined at the corruption trial. Thisfurther strengthens that the principle of equality before the law in Indonesia is still veryconcerning. The existence of differences in decisions influenced by social strata is verythick in corruption. With consideration of the principle that everyone should be equalbefore the law. Nothing can influence the decision, considering the magnitude of the lossand the impact of the crime itself.Adhering to the principle of equality before the law (equal position in law andgovernment), there should be no defendants of corruption crimes who receive preferentialtreatment between one actor and another who are subject to detention by the Court(Judge).This study will examine the subject matter according to the scope andidentification of problems through a normative juridical approach. In this type of legalresearch, the law is conceptualized as what is written in the legislation (law in the book)or the law is conceptualized as legal rules which are standards for behaving or behavingappropriately or inappropriately by using descriptive methods. This research is anormative juridical research on legal systematics. This research is legal systematic andcan be carried out on certain statutory regulations or or written law. Based on thenormative research method, the data source used in this study is a secondary data sourceconsisting of 3 legal materials, namely: primary legal materials, secondary legalmaterials, and tertiary legal materials. Data collected from literature study.Keywords: Application of Principles - Equality Before The Law - Corruption Crimes